Integrated Management System in Safety, Occupational Health and Environment for Clinical Laboratories - Flores Arévalo, Paulo Roberto (2019)
This article proposes an Integrated Management System and discussing about the importance in Safety and Occupational Health in Clinical Laboratories, in order to determinate that factors involve in working safety. Biosafety is a main aspect in working activities and it requires a special training and knowledge in good practices in laboratory to avoid individual and public health risk, subsequently to develop regulation systems procedures or barriers and periodic risk assessment.